2019
DOI: 10.1111/mcn.12916
|View full text |Cite
|
Sign up to set email alerts
|

Dietary guideline adherence during preconception and pregnancy: A systematic review

Abstract: The aim of this study is to determine the level of adherence to dietary guidelines among men and women during preconception, and pregnant women, and factors associated with adherence. Searches were conducted in CINAHL, AMED, EMBASE, and Maternity and Infant Care from inception to March 2018. Observational studies assessing the primary outcome (adherence to dietary guidelines and/or nutritional recommendations) and/or secondary outcome (factors associated with adherence) were eligible. Study quality was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 41 publications
7
83
0
Order By: Relevance
“…Many pregnant women do not follow dietary advice for pregnancy and, as part of this work, we found that most women reported at least one undesirable dietary practice during pregnancy. 10,14 The findings of our study confirm extensive previous research showing that pregnant women welcome diet, weight, and nutrition-related discussions. 8,23 Clinicians working with pregnant women have a responsibility to incorporate brief nutrition and weight discussions into their clinical appointments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Many pregnant women do not follow dietary advice for pregnancy and, as part of this work, we found that most women reported at least one undesirable dietary practice during pregnancy. 10,14 The findings of our study confirm extensive previous research showing that pregnant women welcome diet, weight, and nutrition-related discussions. 8,23 Clinicians working with pregnant women have a responsibility to incorporate brief nutrition and weight discussions into their clinical appointments.…”
Section: Discussionsupporting
confidence: 87%
“…8,9 The effect of this can be seen in the lack of adherence to recommended healthy dietary intakes for pregnancy internationally. 10 Previous work identified lack of resources and relevant training as barriers to addressing nutrition in practice. [11][12][13] The FIGO (International Federation of Gynecology and Obstetrics) Nutrition Checklist is designed to facilitate brief and relevant nutrition discussions between women and their healthcare professional, in a personalized and consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study are in line with other research showing that there is poor adherence to pregnancy dietary recommendations, including intakes of vegetables, wholegrains, folic acid, and iron. 15,16 Fruit, vegetables, wholegrains, and fish are key components of the Dietary Approaches to Stop Hypertension (DASH) dietary pattern and following this diet has been associated with lower maternal blood pressure, even in women without hypertensive disorders. 17 The most common dietary issue in our study was self-reported fish intake of less than once a week.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, developed countries proposed folic acid supplementation as a strategy to ensure the correct fetal growth [17]. However, several lines of evidence showed that folic acid supplementation was often insufficient in the preconception period, with several negative effects on pregnancy and neonatal outcomes [18].…”
Section: Introductionmentioning
confidence: 99%